Research on the presence of cigarette butts and their leaching of chemical pollutants and microparticles: the case of Dalian, China - Yang, Shanshan; Gu, Chenting; Jiao, Yaqian; Yang, Qiying (Frontiers in Marine Science, 2023)
Cigarette butts (CBs) can contain high amounts of toxic substances such as heavy metals, polycyclic aromatic hydrocarbons (PAHs) and microplastics, all of them can result from the incomplete decomposition of CBs. However, limited research exists on the pollution caused by littered CBs in China and the emissions of toxic substances from different Chinese cigarette brands.Therefore, the main objective of this study was to assess the quantity of CBs littered in Dalian city, China, and to evaluate the emissions of heavy metals, PAHs, and microplastics from different cigarette brands. During the survey, a total of 10,591 CBs items and 35 cigarette brands were collected. ICP-MS analysis confirmed the presence of 17 types of heavy metals in the highest abundance brand of CBs, with concentrations ranging from 0.02 μg/L (U and La) to 395 μg/L (Mn). In the lowest abundance brand of CBs, 15 types of heavy metals were detected, with concentrations ranging from 0.08 μg/L (U) to 297 μg/L (Mn). Additionally, a total of 9 PAHs, including compounds such as naphthalene and acenaphthylene, were detected in both the highest and lowest abundance brands of CBs using HPLC-MS/MS, with concentrations ranging from 0.40 ng/L (Anthracene) to 92.12 ng/L (Naphthalence). Microplastics and particles were also identified by light microscopy and SEM. Based on cigarette consumption data in China, it is estimated that annually 360,000 tons of plastic waste are generated by CBs in the environment. Considering the presence of CBs in urban and beach environments, the release of these toxic substances poses a threat to water resources.